Multiple microbial cell-free extracts improve the microbiological, biochemical and sensory features of ewes' milk cheese. (September 2017) - Calasso, Maria; Mancini, Leonardo; De Angelis, Maria; Conte, Amalia; Costa, Cristina; Del Nobile, Matteo Alessandro; Gobbetti, Marco
Abstract: This study used cell-free enzyme (CFE) extracts from Lactobacillus casei, Hafnia alvei, Debaryomyces hansenii and Saccharomyces cerevisiae to condition or accelerate Pecorino-type cheese ripening. Compositional, microbiological, and biochemical analyses were performed, and volatile and sensory profiles were obtained. Lactobacilli and cocci increased during ripening, especially in cheeses containing CFE from L. casei, H. alvei and D. hansenii (LHD-C) and L. casei, H. alvei and S. cerevisiae (LHS-C). Compared to control cheese (CC), several enzymatic activities were higher (P < 0.05) in CFE-supplemented cheeses. Compared to the CC (1907 mg kg −1 of cheese), the free amino acid level increased (P < 0.05) in CFE-supplemented cheeses, ranging from approximately 2575 (LHS-C) to 5720 (LHD-C) mg kg −1 of cheese after 60 days of CFE-supplemented ripening. As shown by GC/MS analysis, the levels of several volatile organic compounds were significantly (P < 0.05) lower in CC than in CFE-supplemented cheeses. All cheeses manufactured by adding multiple CFEs exhibited higher scores (P < 0.05) for internal structure, acid taste and juiciness than CC samples. This study shows the possibility of producing ewes' milk cheese with standardized characteristics and improved flavor intensity in a relatively short time. Highlights: Multiple freeze-dried cell-free extracts (CFEs) from selected microorganisms were used. Multiple CFEs were used as additional sources of exogenous enzymes. CFEs affected the secondary proteolysis of the cheeses. CFEs affected the levels of several volatile organic compounds. The use of CFEs improved the flavor intensity of the cheeses.